PERANCANGAN SISTEM ADMINISTRASI KEPENDUDUKAN (SAK) BERBASIS WEB DI DESA PASIRJENGKOL KAB.KARAWANG. - nau, Sakia; Ponco Subagyo, Catur; Abu Bakar Sidik, Haris (INFOKOM (Informatika & Komputer), 2024)
Population administration is a series of document arrangement activities on population data. Pasirjengkol village has an important role, namely as a population data manager, currently the village office of Pasirjengkol in handling population data administration processes is still done manually. Management of population data in the village of Pasirjengkol is currently still not maximizing the use of information technology for its management. The system is still manual with processes using Microsoft Word and Microsoft Excel. Of course, there are still many deficiencies in the data processing process, which can slow down the process of adding data, searching for data, storing data, and preparing population reports. Because of this, there is a need for a population data administration system in Pasirjengkol Village, which has previously been observed on the activities taking place there, interviews with several village officials. This Population Administration System uses the waterfall method as a software development method. With the data processing process, users can easily search for data. With this system the performance of population services will increase more quickly, easily and neatly.